Implikasi Penerapan Restorative Justice terhadap Kepastian Hukum dan Perlindungan Hak Korban Residivis Penganiayaan Berat - Igvan Nagif Syahyudin; Moh. Rusdiyanto U. Puluhulawa; Avelia Rahmah Y. Mantali (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses the implications of applying Restorative Justice on legal certainty and the protection of victims' rights in cases involving repeat offenders who have committed serious assault in the jurisdiction of the Tapa Police Sector, Bone Bolango. Normatively, Indonesian Police Regulation No. 8 of 2021, Article 5(e), explicitly prohibits the application of Restorative Justice for offenders who have committed repeat criminal offenses based on court rulings. However, the research findings indicate that in practice, law enforcement officials often exercise discretion to facilitate peaceful resolutions even for repeat offenders, citing the need to maintain social relationships and avoid lengthy litigation processes. This approach raises legal certainty issues, as inconsistencies between written norms and field practices can reduce legal predictability, open the door to discrimination, and weaken both general and specific deterrent effects. From the perspective of victim protection, peaceful agreements in cases involving repeat offenders risk not fully reflecting substantive justice, as victims may be in a vulnerable position due to social pressure or unequal power dynamics. This study concludes that the application of Restorative Justice to repeat offenders needs to be strictly limited through more detailed regulations and effective oversight mechanisms, so that the principles of the rule of law, legal certainty, and victim protection are upheld. Thus, Restorative Justice can remain an important instrument in Indonesia's criminal justice system without compromising legal integrity and public safety.